Lower Bound for the First Steklov Eigenvalue - Montaño, Óscar Andrés (Revista de Ciencias, 2014)
In this paper we ﬁnd lower bounds for the ﬁrst Steklov eigenvalue in Riemannian n-manifolds, n = 2, 3, with non-positive sectional curvature.